Formalisation of the knowledge used in design of software, information and business systems - Čaplinskas, Albertas; Lupeikienė, Audronė (Lietuvos matematikos rinkinys, 2001)
This paper is devoted to the formalisation problems of design knowledge used in business systems, information systems, and software design. It discusses the notions of knowledge and information, introduces the concept of ``know-how’’ knowledge, and proposes to use hierarchical finite state machines as the unified formalism to specify business systems, information systems, and software design strategies.